PENINGKATAN SIFAT FUNGSIONAL PATI SAGU (METROXYLON SP.) MELALUI PENAMBAHAN ISOLAT PROTEIN KEDELAI DAN TRANSGLUTAMINASE - Nurmiati; Sapta Raharja; Prayoga Suryadarma (Jurnal Teknologi Industri Pertanian, 2020)
The limited water absorption of sago starch requires the addition of soybean isolate protein and transglutaminase in its formation into a dough. The purpose of this study was to analyse the effect of addition of soy protein and transglutaminase to sago starch on the water absorption. The study was conducted with the stages of characterization of sago starch, determining the effect of protein concentration of soybean isolates, and determining the effect of the addition of transglutaminase to increase water absorption. The results showed that the addition of 9% concentration of soybean isolate protein could increase water absorption up to 4.60 (g/g). This addition decreased swelling power because the soybean isolate protein has the ability to form a gel lower than starch and also the interaction between starch and protein which limits swelling power. The increase in solubility occured because electrostatic interactions were higher than hydrophobics in the amino acid protein isolates of soybeans. In addition, it decreased peak viscosity, increased final viscosity, decreased viscosity and initial temperature of the gelatinizes. Addition of transglutaminase 2.16 (U/g protein) to sago starch which had been added to soybean isolate protein increased water absorption up to 4.71 (g/g). The addition decreased swelling power and solubility, increased peak viscosity, final viscosity, deterioration of viscosity and initial temperature of gelatinization. Keywords: sago starch, soybean isolate, transglutaminase